Haemolymph electrophoretic pattern of Ascia monuste orseis larvae (Lepidoptera: pieridae) parasitized by Cotesia glomerata (Hymenoptera: braconidae) - Scaglia, M. [UNESP]; Brochetto-braga, M. R. [UNESP]; Chaud-netto, J. [UNESP]; Gobbi, N. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2003)
Cotesia glomerata is a natural enemy of the vegetable plague Ascia monuste orseis and preferably parasites 2nd, 3rd and 4th instar larvae. Parasitism effects on the haemolymph protein profile of Ascia monuste orseis larvae from the 2nd to 7th days were analyzed both qualitatively and quantitatively by SDS-PAGE and Coomassie-Blue binding methods. Quantitative analysis showed a progressive increase in the protein content of about 6.5 and 12.5 times in parasitized and non-parasitized larvae from the 2nd to 5th days, respectively. On the 6th day, a decrease in protein content was observed in both groups, although this decrease was significantly less than the control group that continued to metamorphosis. Meanwhile, parasitized larvae had one more day (7th day) in their larval period to complete parasitoid development, justified by the fact that parasitoid is koinobiont and allows host feeding. On this day, a drastic increase in protein content was detected when the parasitoids left the host. The SDS-PAGE showed proteins of high molecular weight (>120 kDa) on the 5th day of the non-parasitized larvae when they entered pre-pupa stage and on the 7th day of parasitized larvae. Proteins with MW lower than 62 kDa and higher than 27 kDa were absent on the 5th day in control larvae (pre-pupa phase), but present in parasitized larvae. This could indicate a possible relation between these proteins and the host juvenile hormone. Therefore, the presence of C. glomerata influences Ascia monuste orseis development, but its own physiological development is apparently independent of the host, which tends to die when parasitism succeeds.
Keywords: Ascia monuste orseis; Cotesia glomerata; electrophoretic protein profile; haemolymph; natural enemy; parasitism; SDS-PAGE